The study of simple and multiple relationships between emotional intelligence and the styles of leadership (Transformational, transactional and laissez-faire styles) - Naghi Radi Afsouran (آموزش و ارزشیابی, 2014)
In the present descriptive (correlational) study, the relationship between emotional intelligence and leadership styles, namely, transformation, transactional and laissez – fair styles were examined among 320 graduate students of Shahid Chamran University, who were selected by categorial random sampling. The data was gathered through two questionnaires: a 36-item multifactor leadership questionnaire (MLQ) and a 33- item emotional intelligence questionnaire (EIQ). The reliability of the MLQ and EIQ questionnaires were 83% and 56% respectively. The main results indicated that emotional intelligence had a significant negative significant correlation with transformational style and a significant positive correlation with laissez-faire style. This variable did not have any significant correlation with transactional style. Among five dimenshions of emotional intelligence, the dimensions of self-regulation and motivation had significant effects on transformational style. These two dimenshions and the dimension of empathy also had significant effects on laissez-faire style, but only motivation had a significant effect on transactional style of leadership. In this study, the researchers found that the mean scores for affective intelligence and laissez-faire leadership style of the students were lower than average, but the mean scores for transformational and transactional leadership styles of the students were higher than average.